Effect of Bi2O3 contents on magnetic and electromagnetic properties of LiZnMn ferrite ceramics. Issue 8 (July 2022) - Martinson, K.D.; Panteleev, I.B.; Steshenko, K.A.; Popkov, V.I.
Abstract: Soft LiZnMn ferrites with low coercive force values and small grain sizes were developed by the solution combustion synthesis and low temperature sintering technique for microwave applications at a high frequencies. Bismuth oxide was used as an additive to lower the sintering temperature. The examination covered the influence of Bi2 O3 on the crystal structure, microstructure, primary magnetic and dielectric characteristics of lithium-zinc-manganese ferrites. The most promising sample designed for using in microwave devices was produced by sintering at 1075 ℃ temperature for 8 h with added 1.5 wt% Bi2 O3 . These production conditions have yielded 2.98 µm average grain size in a ceramic product, the density is 4.84 cu cm/g, and the coercive force, residual induction, and saturation induction are 58 A/m, 2078.4 G, and 3439.1 G, respectively. In addition, this sample demonstrates a high initial magnetic permeability ( μ i = 168), Curie temperature ( T c = 437.5 ℃), high values of the dielectric loss tangent ( tan δ ɛ = 6.32⸱10 −3 ), ferromagnetic resonance line width (Δ H = 280 Oe) and the resonance line of spin waves (Δ H k = 1.87 Oe). Further increase in the bismuth oxide content allows observing a change in the ceramics microstructure, accompanied by a deterioration in the magnetic and electromagnetic characteristics. Here, the discussion covers the mechanism of change in the functional properties of lithium-zinc-manganese ferrites produced in the conditions of solution combustion with added bismuth oxide. Thus, synthesizing of initial pre-ceramic powder by glycine-nitrate combustion and subsequent low-temperature sintering with added bismuth oxide is a novel efficient technique of producing advanced soft high-frequency LiZnMn ferrites.